Warning System and Automatic Engine Cut off Control Deveploment for Heavy Machine; A Case Study on KOMATSU PC130F-7 - Prayitno, Adhy; Masykuri, Imron (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2019)
An alert and automatic engine cut-off system is an integrated device to prevent the machine from experiencing sudden damage while operating. This system works using feedback principles controller as one component of the regulatory system that functions to process the feedback signal and the reference input signal or error signal becomes a control signal. The purpose of this study is to design a preventive system as a form of controller development for the heavy machine. As a case study, the system is employed on Komatsu PC130F-7 Excavator for engine cut-off functions if there are errors or abnormal engine oil levels and pressures. Komatsu PC130F-7 Excavator is heavy equipment with the highest population in the area of plantations and industrial plantations, especially in Riau and surrounding areas. The controller created is the development of an existing controller on the Machine by adding the engine cut-off feature if there are abnormal oil levels and pressures, and also as an alternative solution to the current problems, that is for safety and preventing more serious damage to the engine. The oil level sensor will be active if the oil level is below the low on the H-L (high-low) measuring stick, and the oil pressure sensor will read if the oil pressure is below 0.49 kPa (0.5 kg / cmÂ²). This design has two inputs, that is a voltage of Â± 15 volts on the path of the engine oil level sensor and oil pressure sensor. This voltage is used as an input that activates the relay work to respond to lower engine speed from 1880 rpm to 950 rpm and continued by the timer work as a time lag regulator to cut off the electricity on the starting engine line so that the engine will automatically stop turning and shut down.